Mental Health in Adults Attended at a Reference Center in Chiapas, México, 2012-2018 - Nájera-Ortiz, Juan C. (2023)
Objective. To determine the frequency of mental health disorders and their relationship with socio-demographic variables and consumption of alcohol and tobacco in adults seen at the Mental Health Care Unit “San Agustín” in Tuxtla Gutiérrez, Chiapas, during the period 2012-2018. Method. Cross-sectional study that included 4612 adults within a range of 18-60 years old attended at Unit’s outpatient service during the above mentioned period. Results. Fifty percent of the total of probands were women, 60% within a range of 18-39 years old. The most frequent disorders were schizophrenia (31.2%), mood (24.1%), and anxiety (21.9%). Variables such as age, sex, family history, and alcohol and illicit drug use were associated with the presence of the most frequent disorders. Similarly, mood disorders presented a higher prevalence among young people and women. Conclusion. The trend regarding the most prevalent disorders in this study, as well as some associated factors are consistent with those found in other countries of the region, which, in turn, can be considered as a relevant component of better strategies to improve care procedures for the Chiapas population’s sectors excperiencing mental health problems.